The Role of ICT in Enhancing Modern Teaching Practices in Elementary Schools - Anastasopoulou, Eleni; Katsonis, Nikolaos; Stavrogiannopoulou, Maria; Travlou, Chrysi; Mitroyanni, Evangelia; Tsogka, Danai (Technium Social Sciences Journal, 2024)
Information and Communication Technology (ICT) has become an integral part of modern education, especially in elementary schools. This paper explores the impact of ICT on teaching methodologies, student engagement, and educational outcomes in elementary settings. By integrating ICT tools, educators can create more interactive and engaging learning environments, cater to diverse learning needs, and prepare students for the digital age. The paper examines various ICT applications, their benefits, and challenges, and provides recommendations for effective implementation.